Social Factors and Students Attitude towards Adolescents’ Pregnancy: A Case Study of Abak Local Government Area of Akwa Ibom State, Nigeria - A, Archibong, Gertrude; O, James, Idopise (American Journal of Social Sciences and Humanities, 2019)
The study examined social factors and students’ attitude towards adolescent pregnancy, in Abak Local Government Area of Akwa Ibom State. Two research questions were raised and answered using descriptive statistics, and two null hypotheses were formulated and tested using t-test statistics at 0.05 level of significance. The study adopted an ex-post facto survey research design. The population comprised 2,961 Senior Secondary Two (SS2) students in the ten (10) public secondary schools in the area of the study. A sample of 328 SS2 students was selected statistically using Taro Yamane sampling procedure. A proportionate random sampling technique was used to select 8 out 10, representing 80% in the area of study. The instrument used for data collection was the researchers’ developed questionnaire entitled, “Social Factors and Students Attitude towards Adolescent Pregnancy Questionnaire (SFSAAPQ)”. The study found a significant influence of social factor variables of peer relationship and parent-child sex education on students’ attitude towards adolescent pregnancy in the study area. It was concluded based on the findings that, social factor variables such as, peer relationship and parent-child sex education have significant influence on students’ attitude towards adolescence pregnancy in the study area. It was therefore recommended that, parents should educate their children on issues related to sex particularly at early stage of development so as to prepare them for any inappropriate sexual relationship that may lead to early pregnancy.